How Women Must Write : Inventing the Russian Woman Poet - Hasty, Olga Peters (Book collections on Project MUSE., 2020)
"'How Women Must Write' studies how women who make poems are variously invented in nineteenth and early twentieth-century Russia. The inventors include women poets themselves, readers who derive poets of their own design from women's poems, and male poets who fabricate women and write poems on their behalf. These distinct vantage points on how the woman poet is constituted foreground the complex interactions between writing women and their readers within ever-shifting social, political, and cultural power structures. Hasty's exploration takes us from an emphatically male Romantic age to a modernist period preoccupied with women's creativity but also its containment. Each chapter studies an episode from Russian cultural history that concretely registers women poets' engagements with disincentives. Part one describes the successes and vulnerabilities of Pavlova and Rostopchina who lay groundwork for women writing after them. Part two examines two women invented by men: Cherubina de Gabriak and Briusov's Nelli, who reflect the establishment's efforts to retain command over women's writing in the Silver Age. Part three studies Marina Tsvetaeva's and Anna Akhmatova's challenges to male authority. These are not passive victims of gender-driven limitations, but purposeful actors realizing themselves creatively and advancing the woman poet's cause. The book will appeal to the general reader as well as specialists in Russian literature, women's studies, and cultural history."--